Perception of an Academic Education focused on constant Scientific Researchat the National University of San Marcos - Pino Romero, Neisser (2018)
In this research article, the aim is to collect the perception of scientific research in the academic education of university students, which is the door to continuous scientific research that must be carried out in order to seek an innovation of scientific and technical knowledge and methods and perspectives that relate science and society. The scientific research reflected in scientific articles from undergraduate training, and with more emphasis on postgraduate training should be the academic support for the development of the country. Therefore, how important is the scientific research that must be done to achieve a better education in society. JEL Classification Codes: I21.